Influence of the exhaust gas turbocharger on nano-scale particulate matter emissions from a GDI spark ignition engine. (5th February 2015) - Cucchi, Matteo; Samuel, Stephen
Abstract: The influence of the exhaust gas turbocharger on nano-scale Particulate Matter (PM) number emissions from a Gasoline Direct Injected (GDI) engine is investigated at fixed exhaust gas dilution ratio for a matrix of three engine speeds and four engine load operating points. Experimental repeatability is assessed by means of the Coefficient of Variation (CoV) from three independent measurements for every test point. A hypothesis test on the difference between total number count before and after the turbine shows that there are statistically relevant variations for most operating points. A reduction in PM total number count at low load is observed, and an increment at high load. It is conjectured that as fuel injection pressure and duration increase with load, a larger share of volatile particulate matter is produced, which then undergoes nucleation as the exhaust gas expands through the turbine. At the same time, the centrifugal action within the turbocharger is believed to promote particle agglomeration and growth, and fragmentation of micro-scale particles. Experiments with variable dilution ratio at a fixed engine test point show that changes in dilution ratio affect repeatability of the emissions measurements only marginally. Yet, a hypothesis test on the variation of total number count with dilution shows that PM number counts are systematically affected by changes in dilution ratio. Furthermore, a hypothesis test also shows that the impact of the turbocharger on total number emissions is statistically relevant regardless of the dilution ratio adopted. Graphical abstract: Highlights: Nano-scale PM from a TGDI engine is measured with a particulate spectrometer. Hypothesis test proves statistically relevant differences in PM across the turbine. As engine load increases PM number concentrations increase across the turbine. Particles nucleation and agglomeration are thought to occur across the turbine. Hypothesis test proves turbine influence regardless of exhaust gas dilution level.